MENGAKOMODASI KERAGAMAN SISWA: STRATEGI PEMBELAJARAN SEJARAH BERDIFERENSIASI PRODUK UNTUK MENINGKATKAN MOTIVASI BELAJAR - Utama, Taqwa Ridlo (Historis : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan Sejarah, 2025)
The current educational paradigm marks a significant shift with the introduction of the Kurikulum Merdeka, which provides educators with greater freedom to customize lesson plans and evaluations according to the needs and preferences of each student. In this context, the concept of Differentiated Learning becomes a crucial milestone. This research aims to implement and evaluate differentiated product learning strategies to enhance student learning motivation in a classroom setting. The method used is Classroom Action Research (CAR), which involves four stages: planning, implementation, observation, and reflection. Data were collected through observations, document studies, and questionnaires. The results show a significant improvement in student learning motivation. There was a noticeable increase in the "Good" category between the pre-cycle and the first cycle, from 4 students (11%) to 30 students (88%). There was a significant decrease in the "Fair" category from 24 students (71%) to 4 students (12%), indicating positive improvement. A similar trend also occurred in the "Poor" category, with a decrease from 6 students (18%) in the pre-cycle to none in the first cycle, demonstrating positive development in student learning motivation.